Review of Human Resource Management Function of Front Line Manager - Liu, Yingying (Scientific Research, 2017)
Front Line Managers (FLMs) are the managers of staff at the grass-roots level at the forefront of performing management activities, who play an important role in the achievement of enterprise’s whole objective and the implementation of enterprise plan to the individual staff and first-line staff. With the development of management practice, FLMs are beginning to shoulder part of the human resources management responsibilities. The paper summarizes the research status of human resource management function of FLMs from the perspective of human resources management, and outlooks the future research direction.
Keywords: FLMs; Human Resources Management; Human Resources Management Effectiveness